The mystery of the Banshee towers - Blyton, Enid. (b, 2013)
The Five Find-Outers and dog join Ern to visit Banshee Towers in their holidays. Bets and Ern love the sea paintings in the big house, and when they notice something strange about them, the Five Find-Outers are off on another mystery.
Keywords: Five Find-Outers (Fictitious characters) -- Juvenile fiction; Detective and mystery stories; Children's stories